Cornelius Castoriadis e l'immaginario democratico Dall'Atene di Pericle alla città secolare del libero mercato - Cornati, Dario (Teologia, 2025)
The article aims to give voice and prominence to Cornelius Castoriadis' strong criticism of the current form of democratic institutions in their process of extinguishing the will of the people within the mystique of liberal political representation. After weighing his role as a leading figure in the drafting of the European economic program - between the 1960s and 1990s -, and nevertheless appreciating the excellence of his humanistic education, the text seeks to reconstruct the prophetic relevance of his denunciation by touching on four cardinal points of his thought: 1) his ontological background; 2) his anthropology based on imagination; 3) his affection for the polis of Athens; 4) his relentless struggle against the bureaucratic drift of the time.